2008
DOI: 10.1002/star.200700634
|View full text |Cite
|
Sign up to set email alerts
|

Pasting Behavior of Amylose, Amylopectin and Their Mixtures as Determined by RVA Curves and First Derivatives

Abstract: The relationship between amylose to amylopectin ratio and functional properties of maize starch blends (system I) and "model mixtures" (system II) made of waxy and high amylose maize starch were investigated using the Rapid Visco Analyser (RVA). A 4-5% difference in amylose content caused significant difference in RVA curves and their first derivatives. Based on the first derivative of the RVA curves four different parameters (Peak 2, Peak Time 2, Peak 3, Peak Time 3) were defined. Peak viscosity and parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 18 publications
(43 reference statements)
9
71
1
Order By: Relevance
“…However, the variation in enthalpy was higher for this pea cultivar when compared with those cited by the same authors for the mutant r pea genotype. Composition and characterization of pea and chickpea starches POLESI, L. F. et al www.ital.sp.gov.br/bj This association between lower viscosities and higher amounts of amylose in starch has also been reported in the literature (SONG and JANE, 2000;JUHÁSZ and SALGÓ, 2008). Hedley et al (2002) found low viscosity values when studying the starch from the mutant r pea genotype.…”
Section: Polesi L F Et Alsupporting
confidence: 53%
“…However, the variation in enthalpy was higher for this pea cultivar when compared with those cited by the same authors for the mutant r pea genotype. Composition and characterization of pea and chickpea starches POLESI, L. F. et al www.ital.sp.gov.br/bj This association between lower viscosities and higher amounts of amylose in starch has also been reported in the literature (SONG and JANE, 2000;JUHÁSZ and SALGÓ, 2008). Hedley et al (2002) found low viscosity values when studying the starch from the mutant r pea genotype.…”
Section: Polesi L F Et Alsupporting
confidence: 53%
“…It has previously been reported that AC is positively (Singh et al, 2006;Tran et al, 2001) and negatively (Chung et al, 2011;Juhász & Salgó, 2008;Tan & Corke, 2002) correlated with PV. Using data from IRRI's quality evaluation program, Figure 5a shows that AC does affect PV for non-waxy varieties, in agreement with previous reports (Larkin et al, 2003;Yan et al, 2005).…”
Section: Effect Of Amylose On Functional Propertiesmentioning
confidence: 87%
“…Derived curves were evaluated as introduced by JUHÁSZ and SALGÓ (2008). Pearson's correlation coeffi cients were calculated at every data point between the viscosity values of the single curves and the corresponding AX concentrations of the samples.…”
Section: Methodsmentioning
confidence: 99%
“…This method of evaluation was effectively used for rice fl our (MEADOWS, 2002) and maize starch/amylose/amylopectin mixtures (JUHÁSZ & SALGÓ, 2008). Derivative viscograms interpret the rate of viscosity changes during pasting and are helpful to recognize the fi ne details of the gelatinization process and to understand better the physical and chemical interactions between the starch components during gelatinization (JUHÁSZ & SALGÓ 2008).…”
Section: Acta Alimentaria 45 2016mentioning
confidence: 99%
See 1 more Smart Citation